JUTA, CJ Inventory of documents - JUTA, CJ (ARCA, 2018)
Doctor of Philosophy; Senior lecturer Political Science University of Natal. Fragmentary documents reflecting the wide interest of Dr Juta; History of Natal; Politics in general (the documents were compiled by several politicians and political parties.
COVERAGE 1899-1963.
Keywords: JUTA, CJ